The Effectiveness of Liquid NPK Fertilizer on the Growth and Yield of Corn Plants - Krismawati, Amik; Aisyawati , Lina; Antarlina, S. S.; Arifin, Zainal (Research Highlights in Agricultural Sciences Vol. 1, 2022)
The study sought to ascertain the efficacy of liquid NPK fertilizer on corn plant growth and yield. To improve nutrient balance in the soil, in addition to the application of N-inorganic fertilizers in recommended doses, P and K fertilizers are needed to increase corn crop production. The Experiment was conducted in lowland at Malang Regency on DS II the 2018 with research plots of 6 m x 4 m compiled with randomized block design, 4 times, namely, A: no fertilization, B: 300 kg Urea/ha + 50 kg SP-36/ha + 200 kg Ponska/ha (comparison), C: 300 kg Urea/ha + 50 kg SP-36/ha + 3 ml liquid NPK/l water, D: 300 kg Urea/ha + 50 kg SP-36/ha + 4 ml liquid NPK/l water, E: 300 kg Urea/ha + 50 kg SP-36/ha + 5 ml liquid NPK/l water, F: 300 kg Urea/ha + 50 kg SP-36/ha + 6 ml liquid NPK/l water, G: 300 kg Urea/ha + 50 kg SP-36/ha + 7 ml liquid NPK/l water, and H: 300 kg Urea/ha + 50 kg SP-36/ha + 8 ml liquid NPK/l water. The findings revealed that liquid NPK fertilizer by spray on plants is very effective in increasing the growth and yield of corn plants. Administration of liquid NPK fertilizer using a 4-ml-per-liter water rate (6 applications) Combining 300 kg of urea and 50 kg of SP-36 per hectare (D treatment) increases corn production by 9.10 t/ha dry grains and has an R/C ratio of 3.55, making it economically viable.